176k views
3 votes
PLEASE!!! I JUST REALLY NEED HELP RIGHT NOW! T∆T

Using the 45o -45o -90o triangle theorem, solve this triangle.​

PLEASE!!! I JUST REALLY NEED HELP RIGHT NOW! T∆T Using the 45o -45o -90o triangle-example-1

2 Answers

4 votes

Answer:

Explanation:

take 45 degree as reference angle

using cos rule

cos 45=adjacent/hypotenuse

1/
√(2)=24/k(do cross multiplication)

24*
√(2) =k*1

24
√(2) =k

User Napon
by
4.6k points
0 votes

Answer:


k = 24 √(2)

Explanation:

Given is a 45° - 45° - 90° triangle.

According to the 45° - 45° - 90° triangle theorem, measure of the side opposite to 45° angle is equal to
(1)/(\sqrt 2) times of the hypotenuse.


\therefore 24 = (1)/( √(2) ) k \\ \\ \therefore \: 24 √(2) = k \\ \\ \therefore \:k = 24 √(2)

User Stefan Koell
by
4.6k points